Women and Men in Rural Finance in the Syrian Arab Republic: State-Owned Banking vs. Self-Managed Microfinance - Hans Dieter Seibel; Annina Lubbock; Henri Dommel (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 2002)
Policymakers in Syria are seriously concerned (a) about social equality and equal opportunities for women and men; and (b) about the effectiveness of financial institutions in providing adequate services to men, women and youth to fight poverty and reduce unemployment. Considerable social progress has been achieved in terms of social indicators; but wide gaps persist in terms of economic opportunities for women and men. A private banking law, presently before parliament, is expected to lead to thourough reforms of state-controlled banks
Keywords: 330; Mikrofinanzierung; Ländlicher Finanzmarkt; Agrarkredit; Geschlecht; Frauenpolitik; Syrien